Introducing Climate Change and Climate Smart Agriculture to SMEs - Lessons learned - Jaquet, Stephanie; Derenoncourt, Marie Ena (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The Gender Smart Agriculture Challenge aimed to create gender-responsive Climate-Smart Agriculture (CSA) business models in Senegal, with the goal of attracting private investor capital.